Anti-migration enhanced tracheal stent design, rapid manufacturing and experimental tests. Issue 1 (18th January 2016) - Fiorentino, Antonio; Piazza, Cesare; Ceretti, Elisabetta
Abstract : Purpose: – The purpose of this paper is to focus on tracheal stent production with the aim of investigating the available devices and improving their performances. The biomedical field is a continuously growing area of the market always in search of the most innovative and competitive solutions for healthcare. Beside the actual critical period of the world economy, it shows continuous improvements in research and innovation. Design/methodology/approach: – Within a market analysis and the collaboration between engineering and biomedical research fields, it was outlined a new product concept able to satisfy the patient's and physician's requirements with the focus on the enhancement of the stent anchorage. As a result, the concept of a custom- or tailor-made stent was identified as a potential solution. Moreover, additive technologies were identified as the economically sustainable processes for manufacturing these innovative stents. In the present paper, different types of stents were derived from the proposed concept, they were designed, manufactured and their anchorage capability was tested. In particular, the procedures adopted for their design are described and discussed. Moreover, silicone fused deposition modelling was adopted and two types of deposition method, namely, layer-by-layer and continuous, were used to manufacture the devices identifying their pro, cons and limits. Finally, the stents were tested against migration and results were compared with one of the most widely used today. Findings: – The results show how additive manufacturing allowed to manufacture more efficient and migration resistant stents. Originality/value: – It is expected that this new stent design will reduce the risk of complications in stenting, as granulation, thanks to a more uniform stress distribution on the trachea tissues. These improved characteristics will allow to enhance the quality of both the product and the patient's healthcare.